Improving the forecasts of European regional banks' profitability with machine learning algorithms - Ulrich Haskamp (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
Regional banks as savings and cooperative banks are widespread in continental Europe. In the aftermath of the financial crisis, however, they had problems keeping their profitability which is an important quantitative indicator for the health of a bank and the banking sector overall. We use a large data set of bank-level balance sheet items and regional economic variables to forecast protability for about 2,000 regional banks. Machine learning algorithms are able to beat traditional estimators as ordinary least squares as well as autoregressive models in forecasting performance. – – Regionalbanken, wie Sparkassen und Volksbanken, sind in Kontinentaleuropa weit verbreitet. Wie andere Banken auch, hatten sie nach der Finanzkrise Schwierigkeiten ihre Profitabilität zu halten. Profitabilität stellt einen wichtigen quantitativen Indikator für den Zustand einer Bank beziehungsweise für den gesamten Bankensektor dar. Wir nutzen eine große Zahl von Bankbilanzdaten und ökonomischen Regionaldaten, um die Profitabilität von ungefähr 2.000 europäischen Regionalbanken vorherzusagen. Es zeigt sich, dass Machine Learning-Ansätze genauere Prognosen liefern können, als traditionelle Modelle, wie die Methode der kleinsten Quadrate oder autoregressive Modelle.
Keywords: C53; C55; G21; 330; profitability; regional banking; forecasting; machine learning